Beyond correlation: Unveiling the causal link between streetscapes and recreational walking/cycling - Lingzi Xu; Haochen Shi; Wenbo Lyu; Yan Zhang; Hongbo Zhao (Journal of Transport Geography, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

A numerical study of the possible influence of the ice nucleation process on the bolt-from-the-blue lightning production - Qianwei Zhao; Zheng Shi; Yanfeng Fan; Xuedong Cui; Haochen Chen; Wenzhong Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Retraction notice to “Mobilization of contaminants: Potential for soil remediation and unintended consequences” [Sci. Total Environ. 839 (2022) 156373] - Manish Kumar; Nanthi Bolan; Tahereh Jasemizad; Lokesh P. Padhye; Srinidhi Sridharan; Lal Singh; Shiv Bolan; James O'Connor; Haochen Zhao; Sabry M. Shaheen; Hocheol Song; Kadambot H.M. Siddique; et al. (Science of The Total Environment, 2026)

Retraction notice to “Boron contamination and its risk management in terrestrial and aquatic environmental settings” [Sci. Total Environ. 894 (2023) 164744] - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2026)

Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

ConsenNet–based fully decentralized MARL for residential flexibility coordination in resilient community microgrids - Peixian Huang; Cheng Ma; Mingze Xu; Haochen Hua; Jin Zhao; Shunbo Lei (Energy and Buildings, 2026)

Occurrence, seasonal variability, and ecological risk of emerging contaminants in estuarine and nearshore waters around Hainan Island, China - Haochen Niu; Yuehua Huang; Sichen Li; Xueqing Zhou; Chuhan Sun; Hongwei Zhao (Marine Environmental Research, 2026)

Research on expansion of hydraulic fractures based on reservoir architecture: implications for well spacing in the northern Ordos Basin tight gas reservoir - Lei Bao; Qi Chen; Yuming Liu; Haochen Liu; Minghao Zhao; Xinqiang Liu; Jiagen Hou (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

The influence of potassium ions on CuMgAlOx catalysts during hydrodeoxygenation of biomass pyrolysis oil - Zhongxi Jiang; Mingyue Yang; Xiaowei Bai; Haochen Yang; Zhenghua Dai; Yunpeng Zhao; Jian Li (Biomass and Bioenergy, 2026)

Mechanobiological Response of Osteocyte TRPV4 Base on the Piezoelectricity of Bone Matrix - Shibo Gu; Yuqing Duanwang; Yinuo Zhao; Shuo Gao; Haochen Li; Xinrui Wu; Quanyou Zhang; Yanru Xue; Meng Zhang; Xiaogang Wu; Weiyi Chen (Annals of Biomedical Engineering, 2026)

Effect of offshore fixed photovoltaic pile foundations on wave fields: A theoretical study - Haochen Zhang; Gao Li; Jing Geng; Xuanlie Zhao (Ocean Engineering, 2025)

DFT-enhanced machine learning for accurate PLQY prediction and inverse design of novel MR-TADF materials - Haochen Shi; Yiming Shi; Guangjun Zeng; Haichang Wang; Yumei Hu; Bo Qiao; Zhiqin Liang; Suling Zhao; Man-Chung Tang; Dandan Song (Chemical Engineering Journal, 2025)

Enhancing the Feature Representation of Protein Sequence Descriptors in Protein-Protein Interaction Prediction - Hoai-Nhan Tran; Nguyen-Phuc-Xuan Quynh; Haochen Zhao; Jianxin Wang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Occurrence, distribution characteristics, and potential ecological risks of perfluorinated compounds in major estuaries and adjacent offshore areas in Hainan Island - Yanhong Hu; Yuehua Huang; Haochen Niu; Hongwei Zhao (Marine Environmental Research, 2025)

Construction of efficient proton channels with silica-encapsulated carbon nanotubes for proton exchange membrane water electrolysers - Min Huang; Yang Li; Haochen Lu; Siyi Gao; Felix Kwofie; Xinyao Guo; Quentin Meyer; Yi Wang; Chuan Zhao; Nanwen Li; Yi Cheng (Chemical Engineering Journal, 2025)

Mitigating overestimation in lithium-ion battery recycling LCA: The critical role of ex-post data and operational parameters - Shiyu Wang; Fengyin Zhou; Jingjing Zhao; Hongya Wang; Xin qu; Muya Cai; Haochen Wang; Xu Wang; Dihua Wang; Huayi Yin (Chemical Engineering Journal, 2025)

Compounding effects of Lake and urbanization on summer precipitation in the Greater Chicago area - Jiali Wang; Zhao Yang; Theron Moustakes; Haochen Tan; Rao Kotamarthi; Alberto Martili; Robert Jackson; Paytsar Muradyan; Scott Collis; Joseph O'Brien; Dev Niyogi; Ashish Sharma (Urban Climate, 2025)

Integrating AI into OLED material design: a comprehensive review of computational frameworks, challenges, and opportunities - Yiming Shi; Ming Sun; Haochen Shi; Zhiqin Liang; Bo Qiao; Suling Zhao; Xuemei Pu; Dandan Song (Science Bulletin, 2025)

High-touch surfaces with moderate contamination levels as key nodes in microbial dissemination - Pengcheng Zhao; Peihua Wang; Tzehau Lam; Nan Zhang; Huanhuan Wang; Haochen Zhang; Jiquan Liu; Yuguo Li (Journal of Hazardous Materials, 2025)

Spatiotemporal variability of soil moisture and its influencing factors in a forested catchment with complex terrain - Haochen Liu; Shangqiang Hui; Yuting Zhao; Yanjia Jiang; Yongliang Qi; Elizabeth W. Boyer; Carlos R. Mello; Li Guo; Hongxia Li (CATENA, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Tensor joint framework enhanced by game-theoretic constrained optimization for skin cancer forecasting - Jinqian Yang; Jie Wen; Haochen Zhao; Jianghui Cai; Xingjuan Cai (Swarm and Evolutionary Computation, 2025)

Advances of Complex Marine Environmental Influences on Underwater Vehicles - Sen Zhao; Haibao Hu; Abdellatif Ouahsine; Haochen Lu; Zhuoyue Li; Zhiming Yuan; Peng Du (Journal of Marine Science and Engineering, 2025)
Underwater vehicles serve as critical assets for global ocean exploration and naval capability enhancement. The marine environment exhibits intricate hydrodynamic phenomena that significantly threaten underwater vehicle navigation safety, particularly in four prevalent complex conditions: surface waves, oceanic currents, stratified fluids, and internal waves. This comprehensive review systematically examines the impacts of these four marine environments on underwater vehicles through critical analysis and synthesis of contemporary advances in theoretical frameworks, experimental methodologies, and numerical simulation approaches. The identified influences are categorized into five primary aspects: hydrodynamic characteristics, dynamic response patterns, load distribution mechanisms, navigation trajectory optimization, and stealth performance. Particular emphasis is placed on internal wave interactions, with rigorous analysis derived from experimental investigations and numerical modeling of internal wave dynamics and their coupling effects with underwater vehicles. In addition, this review points out and analyzes the shortcomings of the current research in various aspects and puts forward some thoughts and suggestions for future research directions that are worth further exploration, including enriching the research objects, upgrading the experimental techniques, and introducing artificial intelligence methods.

Delineating and refining the equity of revealed accessibility of express service amenities: A case study of Guangzhou - Yankai Wang; Quanyu Liu; Tao Mei; Haochen Shi; Miaoxi Zhao; Binbin Sun (Applied Geography, 2025)

Phosphorus addition mitigates the combined negative effects of high temperature and nitrogen stress on corals - Zhuojing Zhou; Huidan Yang; Sichen Li; Haochen Niu; Dongdan Yuan; Hongwei Zhao (Marine Environmental Research, 2025)

Transmission of respiratory diseases in high-metabolic environments: A case study of gym - Haochen Zhang; Pengcheng Zhao; Zhiyang Dou; Boni Su; Yuguo Li; Nan Zhang (Building and Environment, 2025)

Serum trace elements and osteoarthritis: A meta-analysis and Mendelian randomization study - Haoyan Shi; Haochen Wang; Minghao Yu; Jianbang Su; Ze Zhao; Tianqi Gao; Qian Zhang; Yingliang Wei (Journal of Trace Elements in Medicine and Biology, 2024)

Effectiveness of composite fume suppression and deodorizing agents in improving performance and reducing emissions of rubber modified asphalt - Juan Xie; Zheyu Ding; Haochen Luo; Zhenzhen Lu; Shuaihui Li; Xucheng Zhao; Bin Huang; Jinmei Lin (Journal of Cleaner Production, 2024)

Study on high-temperature emission behaviors of crumb rubber modified asphalt: Experimental analysis and molecular simulation approach - Juan Xie; Zheyu Ding; Haochen Luo; Shuaihui Li; Wen He; Xucheng Zhao; Yuetan Ma (Journal of Cleaner Production, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Burning behavior of hydrogen jet flame inhibited by a wire mesh screen - Zhenhua Tang; Zhirong Wang; Hui Xu; Yuhan Xiao; Haochen Lu; Kun Zhao (Process Safety and Environmental Protection, 2024)

Heat-moisture treatment of freshly harvested high-amylose maize kernels improves its starch thermal stability and enzymatic resistance - Zhonghua Gu; Gaomin Cheng; Xianying Sha; Haochen Wu; Xinwei Wang; Renyong Zhao; Qiang Huang; Yinong Feng; Jihua Tang; Hongxin Jiang (Carbohydrate Polymers, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

Machine learning-enabled discovery of multi-resonance TADF molecules: Unraveling PLQY predictions from molecular structures - Haochen Shi; Yiming Shi; Zhiqin Liang; Suling Zhao; Bo Qiao; Zheng Xu; Lijuan Wang; Dandan Song (Chemical Engineering Journal, 2024)

Interaction of composite fume suppression and odor elimination agents with crumb rubber modified asphalt: Inhibition behavior of volatile organic compounds (VOCs) and inorganic fume - Juan Xie; Zheyu Ding; Haochen Luo; Xucheng Zhao; Shuaihui Li; Yuetan Ma (Science of The Total Environment, 2024)

A multi-objective optimization approach for green supply chain network design for the sea cucumber (Apostichopus japonicus) industry - Anqi Ren; Lixingbo Yu; Xintao Zhao; Fei Jia; Fengfan Han; Haochen Hou; Ying Liu (Science of The Total Environment, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

Effects of distinct lipid phases and packaging on alleviating the quality deterioration of surimi gels during frozen storage - Yuxin Wang; Xidong Jiao; Nana Zhang; Bowen Yan; Haochen Ding; Weijian Ye; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

Engineering mesoporous nascent MnO2 colloids for efficient elimination of emerging organic contaminants - Zhuoyue Liu; Dong Cheng; Haochen Yin; Jianghao Zhao; Jiale Zhang; Rongzhi Chen; Shengjiong Yang; Jing Wei; Gen Wang (Journal of Water Process Engineering, 2024)

Research on the operation strategy of joint wind-photovoltaic-hydropower-pumped storage participation in electricity market based on Nash negotiation - Xudong Li; Zhongfu Tan; Junyao Shen; Jiacheng Yang; Wei Fan; Haochen Zhao; Ting Zhang (Journal of Cleaner Production, 2024)

Efficient HCl leaching of platinum group metals from waste three-way catalysts: A study on kinetics and mechanisms - Shiqiang Sun; Wenting Zhao; Chenxi Jin; Wenzhi He; Guangming Li; Haochen Zhu (Environmental Research, 2023)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

RETRACTED: Boron contamination and its risk management in terrestrial and aquatic environmental settings - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2023)

The impact of the streetscape built environment on recreation satisfaction: A case study of Guangzhou - Haochen Shi; Lijun Yu; Yaogeng Xu; Yuqi Liu; Miaoxi Zhao (Journal of Transport Geography, 2023)

One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment - Haochen Qi; Lei Xiao; Jayne Wu; Li Lv; Xinyu Hu; Youyi Zhuang; Xiaoru Liu; Wenci Zhao; Fangshuo You; Jian Zhang; Lei Zheng (Food Chemistry, 2023)

Capturing urban recreational hotspots from GPS data: A new framework in the lens of spatial heterogeneity - Haochen Shi; Hao Huang; Ding Ma; Lu Chen; Miaoxi Zhao (Computers, Environment and Urban Systems, 2023)

Process and mechanism of enhanced HCl leaching of platinum group metals from waste three-way catalysts by Li2CO3 calcination pretreatment - Shiqiang Sun; Chenxi Jin; Wenting Zhao; Wenzhi He; Guangming Li; Haochen Zhu; Juwen Huang (Journal of Hazardous Materials, 2023)

Jet-stirred reactor measurements and chemical kinetic study of ammonia with dimethyl ether - Geyuan Yin; Bo Xiao; Hao Zhao; Haochen Zhan; Erjiang Hu; Zuohua Huang (Fuel, 2023)

Matching supply and demand for ecosystem services in the Yellow River Basin, China: A perspective of the water-energy-food nexus - Dengyu Yin; Haochen Yu; Yangyang Shi; Mingyue Zhao; Jian Zhang; Xiaoshun Li (Journal of Cleaner Production, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)